Bismuth-based photocatalyst for degrading marine micro-plastics and preparation method of bismuth-based photocatalyst

By using the bismuth-based photocatalyst Cs3Bi2Br9/BiOCl heterojunction method in the field of marine microplastic degradation, the problems of complex preparation, high equipment requirements and slow degradation speed in the prior art are solved, and efficient and stable degradation of marine microplastics are achieved. , reduce marine pollution.

CN119488926APending Publication Date: 2025-02-21HAINAN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411638166.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-16
Publication Date
2025-02-21

Smart Images

  • Figure BDA0005137631490000061
    Figure BDA0005137631490000061
  • Figure HDA0005137631500000011
    Figure HDA0005137631500000011
Patent Text Reader

Abstract

The invention provides a bismuth-based photocatalyst for degrading marine micro-plastics and a preparation method thereof, and the preparation method comprises the following three main steps: firstly, mixing a bismuth nitrate pentahydrate solution and a sodium chloride solution with specific concentrations, and carrying out ultrasonic dispersion, hydrothermal reaction and other steps to obtain bismuth oxychloride A; reacting cesium carbonate, octadecene and oleic acid in a nitrogen atmosphere to form cesium oleate, heating a mixture of octadecene, oleic acid, oleylamine, hydrobromic acid and bismuth bromide, injecting the mixture into the cesium oleate, quenching, and collecting quantum dots to form a cesium-bismuth-bromine quantum dot solution B; finally, dispersing bismuth oxychloride A into a solvent, adding the cesium bismuth bromine quantum dot solution B, stirring, washing and drying to obtain the Cs3Bi2Br9 / BiOCl heterojunction bismuth-based photocatalyst. The catalyst is composed of 30% of bismuth oxychloride A and 70% of cesium bismuth bromine quantum dot solution B, can degrade marine micro-plastics under visible light, and has a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a field, and in particular to a bismuth-based photocatalyst for degrading marine microplastics and a preparation method thereof. Background Art

[0002] In recent years, plastics have become an indispensable part of human production and life. The annual production of plastics has exceeded 350 million tons, of which more than 150 million tons will be discarded into the environment. Microplastics are plastic particles with a diameter of less than 5 mm, which can generally be divided into primary microplastics and secondary microplastics. Primary microplastics refer to tiny plastic products produced in human production and life, including man-made plastic products and man-made particles used for raw materials and plastic production; secondary microplastics are small plastic particles produced by larger plastic items after entering the environment due to ultraviolet radiation, temperature fluctuations, mechanical friction and microbial activity. Due to the characteristics of small particle size, light weight and large specific surface area, microplastics are easy to absorb other pollutants and attach microorganisms. Microplastics that adsorb pollutants can be ingested by a variety of marine organisms, causing serious impacts on the marine ecosystem. At present, photocatalytic technology has become one of the important technical means to solve environmental pollution due to its environmental friendliness, high efficiency, strong selectivity and good controllability.

[0003] Among photocatalysts, bismuth oxychloride (BiOCl) has attracted much attention due to its unique optical, electrical and catalytic properties. BiOCl has a layered structure formed by alternating double Cl atomic layers and [Bi2O2] layers along the c-axis, which can also be expressed as [Cl-Bi-O-Bi-Cl]. This layered structure has sufficient space for the polarization of corresponding atoms and atomic orbitals, and the induced dipole moment can effectively separate photogenerated electrons and holes, thereby reducing the recombination rate of photogenerated electrons and holes. However, limited light absorption restricts the development of BiOCl.

[0004] The formation of a heterojunction can modify the surface properties, effectively separate the photoexcited charge carriers, collect more sunlight, and thus improve the photocatalytic activity. Cesium bismuth bromide (Cs3Bi2Br9) exhibits good photocatalytic performance due to its wide bandgap, strong optical controllability, low toxicity and high stability. This method combines BiOCl and Cs3Bi2Br9 tightly to form a heterojunction, which can well separate photogenerated electrons and holes, fully coupling the advantages of the two materials, such as retaining their respective redox capabilities and broadening the light absorption range to enhance photocatalytic activity.

[0005] Chinese patent documents disclose "a photocatalytic ceramic material for marine microplastic treatment and its preparation method", and its application publication number is CN118558314A. This method degrades polypropylene or polyethylene in marine microplastics by loading nano ZnO on porous ceramics. However, this method itself has the problems of complex preparation process and high equipment requirements. Therefore, it is necessary to study and develop a photocatalyst with a simpler preparation method.

[0006] The Chinese patent document discloses "Streptomyces Sudanensis and its application in soil microplastic degradation", and its application publication number is CN118389349A. The invention provides a strain of Streptomyces Sudanensis, which damages the surface structure of microplastics, changes the functional group structure, and produces new products within 60 days. However, the degradation rate of this method is slow and the degradation conditions are limited. Therefore, it is of great significance to prepare a photocatalyst that is more effective in degrading microplastics.

[0007] Therefore, it is of great significance to study a photocatalyst with easily available raw materials, simple preparation process and good photocatalytic degradation effect on microplastics. Summary of the invention

[0008] In view of this, the present invention proposes a bismuth-based photocatalyst for degrading marine microplastics and a preparation method thereof to solve the above problems.

[0009] The technical solution of the present invention is achieved as follows: A method for preparing a bismuth-based photocatalyst for degrading marine microplastics comprises the following steps:

[0010] S1. Dissolve bismuth nitrate pentahydrate and sodium chloride in anhydrous ethanol and ultrapure water respectively to obtain a bismuth nitrate pentahydrate solution with a mass concentration of 40-60% and a sodium chloride solution with a mass concentration of 75-85%, then drip the sodium chloride solution into the bismuth nitrate pentahydrate solution and stir to obtain a mixed solution for ultrasonic dispersion, transfer the mixed solution into a reactor for hydrothermal reaction, wash with deionized water several times, and dry at 50-70° C. for 10-14 h to obtain bismuth oxychloride A;

[0011] S2. Under nitrogen atmosphere, cesium carbonate, octadecene, and oleic acid are placed in a three-necked flask at a mass volume ratio of (0.5-0.9) g / mL:(10-20) g / mL:(2-3), and heated to complete reaction to form cesium oleate. A mixture of octadecene, oleic acid, oleylamine, hydrobromic acid, and bismuth bromide at a mass volume ratio of (20-40) g / mL:(2-4) g / mL:(2-4) g / mL:(0.1-0.3) g / mL is placed in a three-necked flask, and after the temperature is raised to 200-240°C, cesium oleate is rapidly injected into the solution. After 5 seconds, the solution is quenched in an ice-water bath, and the quantum dots are collected by centrifugation. The quantum dots are redispersed in n-hexane to form a cesium bismuth bromine quantum dot solution B.

[0012] S3. After dispersing bismuth oxychloride A in a solvent, add the above-mentioned cesium bismuth bromine quantum dot solution B and stir vigorously, wash with isopropanol, and vacuum dry at 80-100°C to obtain a Cs3Bi2Br9 / BiOCl heterojunction, which is a bismuth-based photocatalyst.

[0013] Furthermore, the volume ratio of the sodium chloride solution and the bismuth nitrate pentahydrate solution in S1 is 20-50:100.

[0014] Furthermore, the ultrasonic dispersion of S1 has an ultrasonic frequency of 20-40 kHz, an ultrasonic power of 70-100 W, and an ultrasonic time of 40-60 min.

[0015] Furthermore, the hydrothermal reaction temperature of S1 is 90-110° C. and the reaction time is 15-20 h.

[0016] Furthermore, the temperature for the complete reaction of S2 to form cesium oleate is 145-155° C. and the time is 0.5-1.5 h.

[0017] Furthermore, the solvent of S3 is selected from ethanol, acetone or dimethylformamide.

[0018] Furthermore, the stirring time of S3 is 10-15h.

[0019] Furthermore, a bismuth-based photocatalyst for degrading marine microplastics comprises the following weight percentages: 30% bismuth oxychloride A and 70% cesium bismuth bromide quantum dot solution B.

[0020] Furthermore, the bismuth-based photocatalyst obtained by the above preparation method is applied under visible light.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] (1) The preparation method of the present invention successfully synthesized a Cs3Bi2Br9 / BiOCl heterojunction photocatalyst with high catalytic activity by finely regulating the reaction conditions and raw material ratios of each step. The catalyst exhibits excellent degradation performance under visible light and can efficiently decompose marine microplastics into small molecules, thereby reducing pollution to the marine ecosystem.

[0023] (2) Advanced technologies such as ultrasonic dispersion and hydrothermal reaction were used in the preparation process to ensure uniform dispersion and high crystallinity of the catalyst particles, further improving its catalytic efficiency and stability. At the same time, high yield and good dispersibility of the catalyst were achieved by optimizing parameters such as solvent selection and stirring time.

[0024] (3) The composition ratio of the bismuth-based photocatalyst is reasonable, and the synergistic effect of bismuth oxychloride A and cesium bismuth bromide quantum dot solution B enhances its photocatalytic performance. This catalyst not only has the ability to efficiently degrade marine microplastics, but also has good environmental adaptability and stability, providing a new and effective means for marine environmental protection.

[0025] In summary, the preparation method of the bismuth-based photocatalyst for degrading marine microplastics has significant advantages such as simple process, convenient operation, high catalytic efficiency, and environmental friendliness, which is of great significance for promoting marine environmental protection and sustainable development. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is the SEM image of the degradation of microplastics;

[0027] In the figure, a is the original plastic, b is 50 mg of degraded plastic, c is 100 mg of degraded plastic, and d is 200 mg of degraded plastic. DETAILED DESCRIPTION

[0028] In order to better understand the technical content of the present invention, specific embodiments are provided below to further illustrate the present invention.

[0029] Unless otherwise specified, the experimental methods used in the embodiments of the present invention are all conventional methods.

[0030] Unless otherwise specified, the materials, reagents, etc. used in the embodiments of the present invention can be obtained from commercial sources.

[0031] Example 1

[0032] A method for preparing a bismuth-based photocatalyst for degrading marine microplastics comprises the following steps:

[0033] S1. Dissolve bismuth nitrate pentahydrate and sodium chloride in anhydrous ethanol and ultrapure water respectively to obtain a bismuth nitrate pentahydrate solution with a mass concentration of 40% and a sodium chloride solution with a mass concentration of 75%, then drop the sodium chloride solution into the bismuth nitrate pentahydrate solution and stir, the volume ratio is 20:100, and the mixed solution is subjected to ultrasonic dispersion, the ultrasonic frequency of the ultrasonic dispersion is 20kHz, the ultrasonic power is 70W, the ultrasonic time is 40min, the mixed solution is transferred into a reactor for hydrothermal reaction at 90°C for 15h, then washed with deionized water several times, and dried at 50°C for 10h to obtain bismuth oxychloride A;

[0034] S2. Under nitrogen atmosphere, 0.814 g of cesium carbonate, 10 mL of octadecene and 2.5 mL of oleic acid were placed in a three-necked flask and heated to 150 ° C for 1 h to form cesium oleate (CS-OA). A mixture of 20 mL of octadecene, 2 mL of oleylamine, 2 mL of oleic acid, 0.1 mL of hydrobromic acid and 0.337 g of bismuth bromide was placed in a three-necked flask and degassed under vacuum at 120 ° C for 1 hour, then the temperature was raised to 210 ° C under nitrogen atmosphere, and 2 mL of cesium oleate was quickly injected into the above solution by vigorous stirring. Within 5 seconds, the mixture was quenched with an ice water bath, and then the quantum dots were collected by centrifugation, washed with n-hexane to remove organic residues, and the quantum dots were redispersed in n-hexane to form cesium bismuth bromide quantum dot solution B;

[0035] S3. After dispersing bismuth oxychloride A in ethanol, add the above-mentioned cesium bismuth bromine quantum dot solution B and stir vigorously for 10 hours. The weight percentage of bismuth oxychloride A and cesium bismuth bromine quantum dot solution B is 30:70. Then wash with isopropanol and dry in vacuum at 80°C to obtain Cs3Bi2Br9 / BiOCl heterojunction, which is a bismuth-based photocatalyst.

[0036] The above 50 mg Cs3Bi2Br9 / BiOCl heterojunction was added into 1 g / L microplastic suspension for degradation.

[0037] Example 2

[0038] A method for preparing a bismuth-based photocatalyst for degrading marine microplastics comprises the following steps:

[0039] S1. Dissolve bismuth nitrate pentahydrate and sodium chloride in anhydrous ethanol and ultrapure water respectively to obtain a bismuth nitrate pentahydrate solution with a mass concentration of 50% and a sodium chloride solution with a mass concentration of 80%, then drop the sodium chloride solution into the bismuth nitrate pentahydrate solution and stir, the volume ratio is 30:100, and the mixed solution is subjected to ultrasonic dispersion, the ultrasonic frequency of the ultrasonic dispersion is 30kHz, the ultrasonic power is 90W, the ultrasonic time is 50min, the mixed solution is transferred into a reactor for hydrothermal reaction at 100°C for 18h, then washed with deionized water several times, and dried at 60°C for 12h to obtain bismuth oxychloride A;

[0040] S2. Under nitrogen atmosphere, 0.814 g of cesium carbonate, 10 mL of octadecene and 2.5 mL of oleic acid were placed in a three-necked flask and heated to 150 ° C for 1 h to form cesium oleate (CS-OA). A mixture of 20 mL of octadecene, 2 mL of oleylamine, 2 mL of oleic acid, 0.1 mL of hydrobromic acid and 0.337 g of bismuth bromide was placed in a three-necked flask and degassed under vacuum at 120 ° C for 1 hour, then the temperature was raised to 210 ° C under nitrogen atmosphere, and 2 mL of cesium oleate was quickly injected into the above solution by vigorous stirring. Within 5 seconds, the mixture was quenched with an ice water bath, and then the quantum dots were collected by centrifugation, washed with n-hexane to remove organic residues, and the quantum dots were redispersed in n-hexane to form cesium bismuth bromide quantum dot solution B;

[0041] S3. After dispersing bismuth oxychloride A in acetone, add the above-mentioned cesium bismuth bromine quantum dot solution B and stir vigorously for 12 hours. The weight percentage of bismuth oxychloride A and cesium bismuth bromine quantum dot solution B is 30:70. Then wash with isopropanol and dry in vacuum at 90°C to obtain Cs3Bi2Br9 / BiOCl heterojunction, which is a bismuth-based photocatalyst.

[0042] Take the above 100 mg Cs3Bi2Br9 / BiOCl heterojunction and add it into 1 g / L microplastic suspension for degradation.

[0043] Comparative Example 1

[0044] Take the above 200 mg Cs3Bi2Br9 / BiOCl heterojunction and add it into 1 g / L microplastic suspension for degradation.

[0045] The test related performance and properties are as follows:

[0046]

[0047]

[0048] The above test results can be found in Figure 1 As a result, it can be seen that the bismuth-based photocatalyst for degrading marine microplastics of the present invention, wherein the layered structure of bismuth oxychloride can effectively separate photogenerated electrons and holes, thereby reducing the recombination rate of photogenerated electrons and holes. Cesium bismuth bromide (Cs3Bi2Br9) has a wide band gap, strong optical controllability, low toxicity and high stability. Cs3Bi2Br9 quantum dots are loaded on the surface of BiOCl nanosheets to form an S-type heterojunction, which can improve the redox ability, broaden the light absorption range, and effectively achieve the degradation effect of microplastics.

[0049] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a bismuth-based photocatalyst for degrading marine microplastics, characterized in that: The following steps are involved: S1. Dissolve bismuth nitrate pentahydrate and sodium chloride in anhydrous ethanol and ultrapure water respectively to obtain a bismuth nitrate pentahydrate solution with a mass concentration of 40-60% and a sodium chloride solution with a mass concentration of 75-85%, then drip the sodium chloride solution into the bismuth nitrate pentahydrate solution and stir to obtain a mixed solution for ultrasonic dispersion, transfer the mixed solution into a reactor for hydrothermal reaction, wash with deionized water several times, and dry at 50-70° C. for 10-14 h to obtain bismuth oxychloride A; S2. Under nitrogen atmosphere, cesium carbonate, octadecene, and oleic acid are placed in a three-necked flask at a mass volume ratio of (0.5-0.9) g / mL:(10-20) g / mL:(2-3), and heated to complete reaction to form cesium oleate. A mixture of octadecene, oleic acid, oleylamine, hydrobromic acid, and bismuth bromide at a mass volume ratio of (20-40) g / mL:(2-4) g / mL:(2-4) g / mL:(0.1-0.3) g / mL is placed in a three-necked flask, and after the temperature is raised to 200-240°C, cesium oleate is rapidly injected into the solution. After 5 seconds, the solution is quenched in an ice-water bath, and the quantum dots are collected by centrifugation. The quantum dots are redispersed in n-hexane to form a cesium bismuth bromine quantum dot solution B. S3. After dispersing bismuth oxychloride A in a solvent, add the above-mentioned cesium bismuth bromine quantum dot solution B and stir vigorously, wash with isopropanol, and vacuum dry at 80-100°C to obtain a Cs3Bi2Br9 / BiOCl heterojunction, which is a bismuth-based photocatalyst.

2. The method for preparing a bismuth-based photocatalyst for degrading marine microplastics according to claim 1, characterized in that: The volume ratio of the sodium chloride solution and the bismuth nitrate pentahydrate solution in S1 is 20-50:

100.

3. The method for preparing a bismuth-based photocatalyst for degrading marine microplastics according to claim 1, characterized in that: The ultrasonic dispersion of S1 has an ultrasonic frequency of 20-40 kHz, an ultrasonic power of 70-100 W, and an ultrasonic time of 40-60 min.

4. The method for preparing a bismuth-based photocatalyst for degrading marine microplastics according to claim 1, characterized in that: The hydrothermal reaction temperature of S1 is 90-110° C. and the reaction time is 15-20 h.

5. The method for preparing a bismuth-based photocatalyst for degrading marine microplastics according to claim 1, characterized in that: The temperature for the complete reaction of S2 to form cesium oleate is 145-155° C. and the time is 0.5-1.5 h.

6. The method for preparing a bismuth-based photocatalyst for degrading marine microplastics according to claim 1, characterized in that: The solvent of S3 is selected from ethanol, acetone or dimethylformamide.

7. The method for preparing a bismuth-based photocatalyst for degrading marine microplastics according to claim 1, characterized in that: The stirring time of S3 is 10-15h.

8. A bismuth-based photocatalyst for degrading marine microplastics, characterized by: The solution comprises the following weight percentages: 30% bismuth oxychloride A and 70% cesium bismuth bromide quantum dot solution B.

9. Use of a bismuth-based photocatalyst obtained by the preparation method according to any one of claims 1 to 7 for degrading marine microplastics under visible light.

Citation Information

Patent Citations

  • Streptomyces sudan and application thereof in soil micro-plastic degradation

    CN118389349A

  • Photocatalytic ceramic material for marine micro-plastic treatment and preparation method thereof

    CN118558314A